Pemanfaatan Limbah Organik Kulit Jeruk (Citrus nobilis) Sebagai Minyak Angin Aromaterapi - Wartomo; Risna Nona; Erina Hertianti; Heriad Daud Salusu; Muhammad Fikri Hernandi; Joko Prayitno; Andi Yusuf; Nisrina Putri Hanifah; Agung Nugrawan Kutana; Irma Wahyuningtyas; Farida Aryani; Nur Maulida Sari (ABDIKU: Jurnal Pengabdian Masyarakat Universitas Mulawarman, 2025)
Orange peel waste is one of the wastes that negatively impacts the environment if left to accumulate and ends up rotting. This will lead to environmental pollution in the surrounding area. One application of utilizing orange peel waste is to process it into essential oil, creating a product with high economic value. This activity aims to provide training on the utilization of orange peel waste, which is known to contain active ingredients, into aromatherapy oil products. The method of the activity is carried out through several stages, including: field surveys and coordination with local parties, the implementation of the activity to produce aromatherapy oil from essential oil waste of orange peels, discussions during the activity, and an evaluation of the activity to assess and analyze the achievement of the community service implementation. The result of this activity is the improvement and understanding gained by the community group through training and socialization in utilizing orange peel waste into products with high economic value for the PKK group from Dasawisma Teratai RT.26 Sei Keledang, Samarinda Seberang District.